(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Mineral wool is one of the most commonly used types of thermal insulation in the European Union at the present, however, it generates massive amounts of waste. From an environmental standpoint, recycling or reuse of insulation materials seems to be a wise solution. This paper aims to study the thermal and structural properties of recycled mineral wool insulation recovered from construction and demolition waste. The thermal conductivity, the basic parameter characterizing thermal insulation materials, was measured using a heat flow meter. Test specimens with various bulk density (in the range 50–120 kg/m3) were made from micro-milled and chopped waste material (cladding of 30 years old building). The obtained results were compared with reference samples (non-contaminated blown mineral wool insulation Supafil Loft 045).